Arduino Controlled Automatic Capacitor Bank for Power Quality Improvement in Household Scale - Zen, Hafidz Nindhom; Ibrohim; Haryudo, Subuh Isnur; Endryansyah (Jurnal Teknik Elektro, 2024)
The use of inductive loads on a household scale, especially in electricity customers with a power of 1300 VA, often leads to low power factor values (cos φ) which degrades power quality. This study aims to design and build an Arduino-based automatic capacitor bank system capable of dynamically improving power quality in 1300 VA household electrical installations. The system integrates an Arduino Nano microcontroller with a PZEM-004T sensor to monitor electrical parameters—such as voltage, current, and cos φ—in real time and automatically controls capacitor switching through relays to provide the most suitable compensation. Experimental results show that the system successfully increased the power factor from an average of 0.75 to 0.97 under varying load conditions. In addition, the implementation reduced reactive power by up to 65% and demonstrated potential savings in electricity bills of approximately 8–12% for household consumers. These findings indicate that the proposed system not only improves power factor close to ideal conditions (cos φ ≈ 1) but also enhances overall energy efficiency and provides tangible economic benefits for household users.